Environmental, Social, and Governance (ESG) Disclosure, Profitability, and Firm Value: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange - Sinta Bella; Lili Syafitri; Reny Aziatul Pebriani (STIE Amkop Makassar, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure and profitability on firm value. The research employs a quantitative approach using multiple linear regression analysis. The population consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period, with purposive sampling applied as the sampling technique. The study uses secondary data obtained from companies’ annual reports and sustainability reports. The findings show that ESG disclosure and profitability simultaneously have a significant effect on firm value. Partially, only certain dimensions of ESG disclosure significantly influence firm value, while other dimensions do not demonstrate a significant effect. This study provides insights for companies on the importance of integrating sustainability practices and financial performance in order to enhance firm value.